Conmemoration and intercession in La Galatea by Cervantes: Book VI (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper examines the moral didactic framework of the sacred Valley ofCypresses, as described in Cervantes’ sixth book, La Galatea. A scrupulous analysis of the form, style and content of this episode reveals the hermeneutic significance of one of the most inspiring episodes of pastoral literature.
Keywords: Cervantes; pastoral prose; symbolism